Laparoscopic management of cervical fibroids: a case series - Shrivastav, Ritika; Shrivastava, Rajesh; Shrivastava, Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Cervical fibroids present unique challenges due to their proximity to the ureter and potential impact on fertility and pelvic anatomy. Laparoscopic techniques offer advantages such as reduced blood loss; shorter hospital stays and faster recovery times as compared to the traditional open methods. We report a case series of 10 cases of cervical fibroid management using laparoscopic methods (laparoscopic myomectomy and total laparoscopic hysterectomy with prophylactic uterine artery ligation in selected cases) performed at our institute Shreeji Hospital, Bhilad between February 2020-January 2024. Laparoscopic hysterectomy was the most common procedure performed (70%), followed by laparoscopic myomectomy (30%). The mean operative time was 96 minutes, with minimal intraoperative complications observed. Postoperatively, patients experienced significant improvement in symptoms such as pelvic pain, abnormal uterine bleeding, and urinary symptoms. Preservation of fertility was achieved in 30% candidates.